Implementation Of Islamic Education Learning Based On Gender At Smp Plus Al Fatimah Bojonegoro - Ahmad Shofiyuddin; Usman Roin (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This research aims to determine the planning, implementation, and supporting factors in teaching Islamic Religious Education based on gender at SMP Plus Al Fatimah Bojonegoro. The research method used a Descriptive Qualitative approach. The findings of the research are as follows: 1) The implementation planning in teaching at SMP Al Fatimah Bojonegoro consists of (a) Analysis of PAI Learning Objectives, (b) Analysis of PAI Educators, (c) Analysis of PAI Students, (d) Analysis of PAI Teaching Materials, and (e) Analysis of Learning Strategies. 2) The implementation of Islamic Religious Education at SMP Plus Al Fatimah Bojonegoro follows the Islamic Religious Education System according to the curriculum set by the Ministry of Education and Culture (Kemdikbud) and the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI). It adjusts the learning materials to the student’s potential, including cognitive, psychomotor, and affective abilities. 3) The supporting and inhibiting factors in the implementation of Islamic Religious Education based on gender at SMP Plus Al Fatimah Bojonegoro are both internal factors (within the students themselves) and external factors (external to the students).